Enhanced Gram-Negative Resistance Gene Survelliance in Clinical Samples using a Rapid Microarray System. (4th October 2017) - Batra, Rahul; Natale, Alex; Otter, Jonathan; Edgeworth, Jonathan
Abstract: Background: Extended-spectrum β lactamases (ESBLs) are clinically significant due to the limited treatment availability and associated increased healthcare costs. They are caused by point mutations arising on chromosomal genes or are encoded from plasmid genes, such as blaCTX-M class genes. These mobile genetic elements can spread to create extensive environment reservoirs, which can, in turn, result in the carriage of resistant bacteria by humans in clinical and non-clinical settings. Methods: All patients admitted to a large London teaching hospital between January and May 2015 were screened. ESBL-carrying organisms were isolated on chromogenic media for ESBL and DNA was extracted. Enterobacteriaceae were analysed for resistance genes using the microarray system Check-MDR CT103XL ® (Check-Points), which detects most carbapenemase and ESBL genes, including plasmid-mediated AmpC genes. Results: A total of 4, 567 patients were approached and 4, 006 screened; prevalence of ESBLs-carrying organisms was 8.2%. Most patients carried only one organism, of which E. coli was the most common (77.8%), followed by K. pneumoniae (8.4%), C. freundii (3.6%) and E. cloacae (2.8%). 20.7% of patients carried more than one ESBL-resistant organism, 3.3% of which belonging to a different species; when of the same species, organisms were considered different based on their resistance genes. The most prevalent ESBL genes identified were the plasmid-mediated blaCTX-M-15 (57.4%) and blaCTX-M-9 (20.7%), and AmpC CMY-2 (6.4%). Notably, 8.6% of isolates carried more than one gene, and 1.4% more than 2 genes, with AmpC genes (CMY-2 and DHA) and ESBL genes (blaCTX-M ) being the most common co-carried genes. Conclusion: The use of the Microarray system Check-MDR CT103XL ® (Check-Point) allows for a rapid and comprehensive identification of resistance genes in clinical samplse. In this study, this system revealed a much more diverse resistance genetic composition of the Enterobacteriaceae population circulating in South London than previously estimated, perhaps due to the unselected patient group screened. It also reveals the co-existence of more than one resistance gene in a proportion of organisms. Moreover, composite genetic profiles could be useful to identify hotspots for transmission or novel risk factors. Disclosures: All authors: No reported disclosures.